2022
DOI: 10.1073/pnas.2202515119
|View full text |Cite
|
Sign up to set email alerts
|

Neural synchronization predicts marital satisfaction

Abstract: Marital attachment plays an important role in maintaining intimate personal relationships and sustaining psychological well-being. Mate-selection theories suggest that people are more likely to marry someone with a similar personality and social status, yet evidence for the association between personality-based couple similarity measures and marital satisfaction has been inconsistent. A more direct and useful approach for understanding fundamental processes underlying marital satisfaction is to probe similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Recently, studies have suggested that IBS, as a dual-brain neural mechanism, plays an important role in the generation and maintenance of romantic relationships. Specifically, in a speed-dating task, IBS predicted the outcome of mate choice [86], and for couples in long-term marriages, IBS strongly predicted marital satisfaction when they watched marital movies [87]. We hypothesize that IBS in those studies was the biological basis for affective bonds.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, studies have suggested that IBS, as a dual-brain neural mechanism, plays an important role in the generation and maintenance of romantic relationships. Specifically, in a speed-dating task, IBS predicted the outcome of mate choice [86], and for couples in long-term marriages, IBS strongly predicted marital satisfaction when they watched marital movies [87]. We hypothesize that IBS in those studies was the biological basis for affective bonds.…”
Section: Discussionmentioning
confidence: 94%
“…Negative feelings that arise will have the effect of anger, dislike, and distance from each other (Olson et al, 2014). Added by Li et al (2022) subjective perceptions, thoughts, and feelings about interpersonal and social interactions are strong predictors of marital satisfaction. Therefore, differences in relationship satisfaction need to be discussed with the partner so that the husband and wife understand each other's wants and needs (Aman et al, 2019).…”
Section: Relationship Satisfaction: Different Perspectives Of Couplesmentioning
confidence: 99%
“…When positive feelings arise in a married couple, it will have the effect of happiness, satisfaction, and pleasant experiences carried out together (Olson et al, 2014;Rusbult & Buunk, 1993) and vice versa when negative feelings arise it will have the effect of anger, dislike, and distance from each other. In 2022, (Li et al, 2022) examined marriage satisfaction predicted using neural synchronization. Based on intersubject synchronization (ISS) of brain responses during watching movies related to married life, and movies that are not related to married life.…”
Section: Introductionmentioning
confidence: 99%

Harmonious Husband and Wife Relationship:

Markus Idulfilastri,
Ramadhanty Khaerunissa,
Marziah Zakaria
2024
Edunity
“…According to Szopiński (1980), marital interactions realised in these three dimensions create a common, threefold psychological quality in the form of: co-understanding, co-feeling and co-acting, which, remaining in feedback, make the psychological experiences of one spouse become part of the experiences of the other (cf. e.g., Li et al, 2022).…”
Section: Marital Bond and Communicationmentioning
confidence: 99%